Climate Information Services Training Manual for Training of Trainers: Promoting Adoption of Pigeonpea, Sorghum and Pearl Millet - Saalu, Faith; Ngwira, Amos; Ganga, Rao NVPR; Rao, KPC; Jacob, Emanuel; Harawa, Rebbie (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This training manual has been developed to guide in providing training on strengthening capacities of agricultural extension officers, lead farmers, Small and Medium Enterprises (SMEs) and Farmer Producer Organizations (FPOs) to scale Climate Information Services (CIS) and Climate Smart Agriculture (CSA) innovations to achieve food and water security as well as building climate resilience.